KEPENTINGAN AMERIKA SERIKAT DALAM MENGHIBAHKAN PESAWAT TEMPUR F-16 KE INDONESIA TAHUN 2014 – 2017 - Jannah, Ushwatul; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is trying to explain about United States of America’s Interest in giving grant F-16 Fighting Falcons to Indonesia in 2014 – 2017. United States and Indonesia are known with good diplomatic relationship among democratic countries in the world. They started the cooperation relationship after the second worldwar ended and stil running well today. This research is using neo-realism perspective, in this perspective of neorealism or so-called structural realism emphasizes the existence of structures in viewing the phenomenon of international relations. For structural realism (offensive and defensive) each country is seen to have the same behavior, policies and interests. This is based on the assumption that every country has a common interest to survive, forcing every country to compete with other countries. For defensive realism, it’s viewing that power is a means of achieving interests, not a final goals and power is only needed sufficiently as needed. With the establishment of good diplomatic relations between the United States of America and Indonesia, through a Joint Commision Meeting the two countries signed an agreement for grant 24 F-16 Fighting Falcons to Indonesia. An intention behind United States of America’s granted those aircrafts are to keep the security stability of Indonesia and Southeast Asia, balancing China’s power and to continue spreading United States of America’s Hegemony.Keyword: F-16 Fighting Falcons, United States of America, Joint Commission Meeting, Neo-Realism